2014
DOI: 10.1002/smll.201303831
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Hair into Heteroatom‐Doped Carbon with High Surface Area

Abstract: Herein, a unique approach to dispose of human hair by pyrolizing it in a regulated environment is presented, yielding highly porous, conductive hair carbons with heteroatoms and high surface area. α-keratin in the protein network of hair serves as a precursor for the heteroatoms and carbon. The carbon framework is ingrained with heteroatoms such as nitrogen and sulfur, which otherwise are incorporated externally through energy-intensive, hazardous, chemical reactions using proper organic precursors. This judic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
112
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(116 citation statements)
references
References 75 publications
4
112
0
Order By: Relevance
“…Examples including cotton [7], pollen grains [8], and sawdust [9] have been used as precursors for various carbon based catalysts, and silk [10], pulse flour [11], honey [12], hair [13] and egg white [14] for the preparation of nitrogen-doped ORR catalysts by pyrolysis and post activations. However, the ORR performance of these catalysts in acid [10] or alkaline [11e14] medium remains lower than Pt/C catalysts, and from a practical point of view commercially uncompetitive.…”
Section: Introductionmentioning
confidence: 99%
“…Examples including cotton [7], pollen grains [8], and sawdust [9] have been used as precursors for various carbon based catalysts, and silk [10], pulse flour [11], honey [12], hair [13] and egg white [14] for the preparation of nitrogen-doped ORR catalysts by pyrolysis and post activations. However, the ORR performance of these catalysts in acid [10] or alkaline [11e14] medium remains lower than Pt/C catalysts, and from a practical point of view commercially uncompetitive.…”
Section: Introductionmentioning
confidence: 99%
“…The potentials of all the electrochemical test results were transferred to the reversible hydrogen electrode (RHE). The relationship between E(vs. RHE) and E(vs. SCE) is shown as follows: E(vs.RHE) = E(vs.SCE) + E SCE + 0.0591 pH (1) where the E SCE at 25 • C is 0.2415 and the pH of 0.1 M KOH is considered as 13. Cyclic voltammetry (CV) or linear sweep voltammetry (LSV) measurements were carried out with a rotating disk electrode (RDE), and a rotating ring disk electrode (RRDE) was used as the working electrode for dual-electrode CV measurements.…”
Section: Electrode Preparation and Electrochemical Measurementsmentioning
confidence: 99%
“…In recent years, fuel cells have been attracting lots of attention due to their high energy conversion efficiency for converting chemical energy into electricity [1][2][3][4][5]. The entire reaction process occurring in fuel cells contains two half-reactions; one is the oxygen reduction reaction (ORR) at the cathode and the other is the hydrogen oxidation reaction (HOR) taking place at the anode.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the surface N-containing functionalities can give ACs acid/base characters, therefore playing a critical role in enhancing capacitance performance by providing pseudocapacitance via reversible redox reaction together with improving wettability between electrodes and electrolytes [23][24][25]. Popular strategies for the synthesis of N-doped ACs (NACs) include the direct carbonization approach, in which N-rich carbon precursors are directly pyrolyzed at high temperature [26], and the post-treatment approach, 4 which attempts to treat carbon with N-containing dopants (such as ammonia, amine, or urea) [11,25,27,28]. The latter approach can maintain the properties of the bulk material, but is time-consuming and results in heterogeneity of N-doping.…”
Section: Introductionmentioning
confidence: 99%